A REVIEW ON UROLITHIASIS - Sharma, Yogesh Kumar; Gilhotra, Umesh Kumar (Journal of Biomedical and Pharmaceutical Research, 2019)
Urolithiasis is the urinary disorder characterized by formation of stone in the urinary tract, urinary bladder and kidneys. Urolithiasis is considered to be a risk of urinary incontinence and may be associated with urinary incontinence. A urinary stone commonly occurs in males and are calculated on the basis of their mineral composition. Approximately 80% of urinary stones composed as calcium oxalate and calcium phosphate. Urinary calculi can cause disruption to the urinary system, hydrophoresis, infections and bleeding. Root stone formation is the result of several mechanisms. Whereas exceeding supersaturation (i.e. free stone formation) is the cause of uric acid or cystine calculi, infection stones result from bacterial metabolism. Renal calculi can be broadly classified in two large groups: tissue attached and unattached. Components in diet increase the risk of stone formation include low intake of fluid and animal protein, sodium, sugar and syrup high corn fruit, oxalate, grape juice, apple juice and cola drinks. Vegetarian diets, spices and liquids may be helpful in treating and prevention and kidney stones. Therefore, the best way to prevent kidney stones is to consume a lot of water and a magnesium rich vegan. Common medications used to prevent urolithiasis do not work for all patients, and many have adverse effects that endanger their long-term use. Managing today’s urolithiasis with open renal surgery is unusual and rarely used, only by the introduction of Extracorporeal Shock wave lithotripsy (ESWL) is useful but it is expensive. Herbs and herbal medicines have created interest among people with its clinically proven effects such as immunomodulation and antimutagenic. Also, abusing synthetic drugs due to serious side effects of the drug has allowed humans to return to nature for safe treatment. Kew words: hydrophoresis, Urolithiasis